2019
DOI: 10.1080/10255842.2019.1634193
|View full text |Cite
|
Sign up to set email alerts
|

Secondary hip dysplasia increases risk for early coxarthritis after Legg-Calve-Perthes disease. A study of 255 hips

Abstract: The biomechanical parameters of the hip joint articular surface were analysed in 141 adult hips after Legg-Calve Perthes Disease, and 114 contralateral unaffected hips (controls), by using HIPSTRESS mathematical models. Geometrical parameters, assessed from anteroposterior and axial radiograms, were used as input to models for resultant hip force and contact hip stress. Results confirm previous indications that head enlargement after the Legg-Calve-Perthes Disease compensates the values of hip stress. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Intra-or extra-articular instability of the joint Usually consequences of poor care and/or injuries causing damage to the hip joint, e.g. inflammation of surrounding tendons, some diseases (Legg-Calvé-Perthes Disease), acetabular labrum lesions or abnormalities [37][38][39].…”
Section: Presence Of Different Malformationsmentioning
confidence: 99%
“…Intra-or extra-articular instability of the joint Usually consequences of poor care and/or injuries causing damage to the hip joint, e.g. inflammation of surrounding tendons, some diseases (Legg-Calvé-Perthes Disease), acetabular labrum lesions or abnormalities [37][38][39].…”
Section: Presence Of Different Malformationsmentioning
confidence: 99%
“…Furthermore, alternative surgical interventions, such as percutaneous transepiphyseal drilling of the femoral head combined with closure of the greater trochanter apophysis, can be an attractive option during early stages of fragmentation (Stulberg type 1–2) as this does not compromise any potential future treatment options [ 17 ]. Similarly, a recent study by Moličnik et al found that biomechanical changes caused by deformed hip articulation play a critical role in the development of secondary hip arthritis in patients with Legg Calve Perthes disease [ 18 ]. The authors found a significant association between the radiological hip containment parameter (small center-edge angle) and an unfavorable distribution of stresses across the hip articulation.…”
Section: Discussionmentioning
confidence: 99%
“…L egg-Calve-Perthes disease (LCPD) and acetabular dysplasia commonly present together and are associated with other hip disorders, including osteochondritis dissecans (OCD) and femoroacetabular impingement (FAI) [1][2][3][4] . The classic OCD definition is an idiopathic, focal disruption of articular cartilage and subchondral bone 4 .…”
mentioning
confidence: 99%